2013
DOI: 10.1177/0956462413513747
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis in a HIV patient receiving ritonavir and inhaled fluticasone

Abstract: We report a case of severe bilateral knee avascular necrosis in a HIV-positive man receiving ritonavir and inhaled fluticasone. This case highlights the need for a thorough medication history in patients on ritonavir-based antiretroviral therapy, especially where multiple prescribers are involved in the patient's care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
1
7
0
2
Order By: Relevance
“…Similarly, a case of bilateral knee AVN in an HIV-infected man receiving inhaled fluticasone and PI was reported by Pollett et al [9].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, a case of bilateral knee AVN in an HIV-infected man receiving inhaled fluticasone and PI was reported by Pollett et al [9].…”
Section: Discussionsupporting
confidence: 56%
“…The risk of AVN is particularly higher in patients on PI therapy; however, the mechanism is unclear [7]. A detailed search of the literature only resulted in three other cases of AVN presenting as a complication of coadministering ritonavir and fluticasone [8][9][10]. Kaviani et al reported a case of a 60-year-old man with AVN of bilateral hips in an HIV-positive patient taking ICS with ritonavir-boosted antiretroviral therapy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Osteonecrosis related to ICS use is very uncommon and available data is limited only to case reports [ 41 - 44 ]. Concomitant use of oral steroids for exacerbation of primary lung conditions such as asthma and COPD increases the risk of osteonecrosis from ICS.…”
Section: Ics and Bone Diseasementioning
confidence: 99%
“…Corticosteroids are metabolised in the liver by Cytochrome P450 enzyme (mainly CYP3A4) system and the medications that induce this enzyme system may increase the systemic bioavailability of steroids leading to toxicity. Increasing use of anti-retroviral medications such as retonavir, which are powerful CYP3A4 inducers, have been found to be associated with a higher risk of ICS-related osteonecrosis [ 43 , 44 ].…”
Section: Ics and Bone Diseasementioning
confidence: 99%
“…1 This may cause iatrogenic Cushing syndrome, suppression of the hypothalamic-pituitary-adrenal (HPA) axis, acute adrenal insufficiency in case of abrupt corticosteroid withdrawal, as well as hypertension, osteoporosis and avascular necrosis. [1][2][3][4][5] We report a case of iatrogenic Cushing syndrome and multifocal osteonecrosis in a patient with HIV1 infection on a ritonavir-boosted antiretroviral therapy (ART) and COPD treated with fluticasone. It is intended to emphasise the importance of the interaction between inhaled corticosteroids and cytochrome P450 (CYP450) inhibitors and its potential severe consequences.…”
Section: Introductionmentioning
confidence: 99%